Evolution of subglacial overdeepenings in response to sediment redistribution and glaciohydraulic supercooling. Issue 2 (22nd April 2013) - Creyts, Timothy T.; Clarke, Garry K. C.; Church, Michael
Abstract: [1] Glaciers erode bedrock rapidly, but evacuation of sediments requires efficient subglacial drainage networks. If glaciers erode more rapidly than evacuation proceeds, a protective subglacial till layer can form to armor the bed. Where glaciers cross overdeepenings, local closed depressions, the bed slope opposes the ice surface and lowers the hydraulic potential gradient that drives water flow. Here, we present results of a dynamic, distributed model of coupled basal water flow and sediment transport to show how overdeepenings evolve over the course of a melt season. We use steady‐state calculations as well as numerical simulations to understand how alluvial bed erosion alters overdeepenings. Numerical results from a modified form of the Spring‐Hutter equations show behaviors that cannot be inferred from either local or steady‐state calculations. In general, opposition of surface and bed slopes lessens sediment transport regardless of ice accretion from glaciohydraulic supercooling. Drainage efficiency strongly affects erosion and deposition rates. Results show characteristic behaviors of flow through overdeepenings such as overpressured water systems and accretion rates compatible with field measurements. Simulations that start with overdeepened glacier configurations progress out of a freezing regime where glaciohydraulic supercooling occurs. This progression indicates that glacier hydrology is more strongly affected by erosion and deposition than by freezing from glaciohydraulic supercooling. We discuss how this outcome affects glacier erosion and sediment transport under modern and past ice sheets. Key Points: We model basal water flow and include erosion of the bed and freeze‐on of ice Sediment transport has a strong influence on subglacial water flow conditions Overdeepenings evolve because of sediment transport rather than ice accretion